Schizophrenia Of the Main Character In Fear Of Rain Movie Directed By Castille Landon - Nijam, Infrida (CV. Kalimasada Group Profesional, 2023)
Literature is something that cannot be separated from people's lives, and films are one of the most popular forms of literary works today. Mental health is an important focus in everyone's life, to maintain and maintain sanity for a better life. This study discusses mental health problems, namely schizophrenia, with films as research objects. The purpose of this study was to find out the early symptoms of schizophrenia, the impact of schizophrenia, and the role of parents in responding to children with schizophrenia. This research uses descriptive qualitative method where the data collected is in the form of words, pictures and not numbers. Schizophrenia has two types of initial symptoms, namely positive symptoms and negative symptoms. In